Cationic poly-l-amino acid-enhanced selective hydrogen production based on formate decomposition with platinum nanoparticles dispersed by polyvinylpyrrolidone. (6th May 2021) - Minami, Yusuke; Amao, Yutaka
Abstract : By using platinum nanoparticles dispersed by polyvinylpyrrolidone (PVP) and cationic poly-l -amino acid, poly(l -lysine) (PLL) (Pt-PVP/PLL), highly selective H2 production based on formate decomposition was achieved about 1.8 times compared to Pt-PVP in a low pH region (pH = 1.8). Abstract : Formate is attracting attention as a hydrogen carrier because of its low toxicity and easy handling in aqueous solution. In order to utilize formic acid as a hydrogen carrier, a catalyst for efficiently and selectively decomposing formic acid into H2 in a low pH region is required. In this work, enhancement of selective H2 production from formate with platinum nanoparticles dispersed by polyvinylpyrrolidone (PVP) and cationic poly-l -amino acid, poly(l -lysine) (PLL), poly(l -histidine)(PLH) and poly(l -arginine)(PLR) (Pt-PVP/PLX; X = L, H or R) in a low pH region was attempted. By using all Pt-PVP/PLX or Pt-PVP for formate decomposition catalysts, the amount of H2 produced was maximized using an aqueous formate solution with a pH of 3.5 (close to a p K a of 3.75 of formic acid). The H2 production catalytic activity of Pt-PVP/PLX (X = L or H) improved compared with that of Pt-PVP in the low pH range (pH = 1.8). By using Pt-PVP/PLL, especially, the amount of H2 produced was improved to about 1.8 times compared to that of Pt-PVP under a pH = 1.8 condition. There was no difference in the electronic states of the platinum nanoparticles in Pt-PVP and Pt-PVP/PLL according to the extended X-ray absorption fine structure and X-ray absorption near edge structure spectra measurements. The amount of H2 produced tended to increase as the PLL content ratio in Pt-PVP/PLL increased and the protonated alkylammonium moiety of PLL in Pt-PVP/PLL attracted the dilute formate ions in the solution to platinum nanoparticles, and the catalytic activity for H2 production was improved under the low pH range.